Evaluation of patient’s perception and experience towards anterior microimplants for intrusion: A questionnaire study - Chinmay, Dave; Bhavnit, Vaghani; Kartik, Patel; Goje, Santosh; Shah, Purvesh; Modi, Bhumi (International Journal of Dental Research, 2017)
Introduction: Implants have gained popularity in orthodontics because they facilitate maximum anchorage with minimum patient Â Â Â cooperation. However, some orthodontists avoid using implants because perception and experience of patients towards such anchorage systems is questionable and is not been fully reported.Aim and objectives: To evaluate the patientâ€™s perception and experience towards the treatment with anterior microimplants for intrusion of anterior teeth using questionnaire.Materials and methods: After considering the inclusion and exclusion criteria, Participants who are undergoing orthodontic treatment with anterior implants for the intrusion of the maxillary anterior teeth was selected for the study. Questionnaire which was validated from ten respondents and subject experts will be given to each participant and asked to fill it. After collection of filled questionnaire, all the data was subjected to statistical analysis.Results: Most of the patients had enough confidence on their orthodontist and did not think to take a second opinion when an anterior implant was recommended. Majority of the patients were concerned to know regarding advantages and disadvantages of anterior Â Â Â Â Â Â microimplant and inquired about the time for the placement of anterior microimplant. More patients were worried about how long the anterior microimplant will remain inserted in their mouth and had fear of local anesthesia. On loading of microimplant, most of the Â Â patients felt pressure at the implant and few felt pain.Conclusion: The procedure was pleasant and comfortable for large number of patients and they did not felt pain after placement of Â Â anterior microimplant. Majority of the patients were satisfied with the treatment and would recommend it to other patients. Highest Â Â number of patients got used to the anterior implant by day 7 followed by day 15. An average acceptable time period for the anterior Â Â microimplant was 12 months. The overall perception and experience by the patients to the placement of anterior microimplant can be rated as expected and good.